MORPHOLOGICAL CHARACTERISTICS OF ROUGH LICORICE (GLYCYRRHIZA ASPERA L.) (Modern American Journal of Biological and Environmental Sciences, 2025)
Glycyrrhiza aspera L. is a perennial xerophytic species belonging to the family Fabaceae and is widespread across the steppe and semi-desert regions of Central Asia. The purpose of this study was to identify, describe, and systematize diagnostically significant morphological traits of the species, taking into consideration its adaptations to arid environmental conditions. A comprehensive field-based morphological analysis was conducted, which included a detailed examination of the stems, leaves, shoots, generative organs, fruits, and the root system. The results showed that G. aspera is characterized by dense pubescence covering all vegetative organs, imparipinnate leaves composed of 7–13 leaflets, raceme-type inflorescences, a cylindrical and pubescent calyx, as well as curved, densely pubescent pods. The well-developed root system—consisting of a strong taproot and horizontally spreading rhizomes—contributes to effective vegetative reproduction and enhances the plant’s competitive capacity within arid ecosystems. The obtained findings are significant for botanical systematics, pharmacognostic research, and the rational and sustainable utilization of this species as a valuable medicinal raw material.